Toward a poetic theory of narration : essays of S.-Y. Kuroda - Kuroda, S.-Y (Trends in linguistics. Studies and monographs, 2014)
The volume consists of six essays by S.-Y. Kuroda on narrative theory, with a substantial introduction, notes, a bibliography and an index of proper names. This is the English version of a French critical edition published by Editions Armand Colin in their "Recherches" series in October 2012, translated from English by Cassian Braconnier, Tiên Fauconnier and Sylvie Patron, edition with an introduction and notes by Sylvie Patron.